Two cases of telbivudine-induced myopathy in siblings with chronic hepatitis B - Eun Hye Kim; Hana Park; Kun Ho Lee; Sang Hoon Ahn; Seung-Min Kim; Kwang-Hyub Han (Clinical and Molecular Hepatology, 2013)
Telbivudine is an L-nucleoside analogue with potent antiviral activity against hepatitis B virus (HBV). Clinical trials have shown that telbivudine has a more potent and sustained antiviral activity with a lower frequency of viral resistance than lamivudine. Although there are several reports concerning the safety profile of telbivudine, most adverse events are described as mild and transient in nature. Here we report two cases of telbivudine-induced myopathy in patients with chronic hepatitis B who were siblings.